Information seeking behaviour of women in the Gulf Cooperation Council universities - El-Maamiry, Ali Amour Suleiman (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2019)
Determining the different cultural factors affecting the information-seeking behaviour on various levels – national, organizational, group and individual is essential to get a holistic idea of how such behaviour is formed. Females in the Gulf Cooperation Council (GCC), which includes the Kingdom of Bahrain, the Kingdom of Saudi Arabia, Kuwait, Qatar, the Sultanate of Oman, and the United Arab Emirates, are educated in different educational systems but have the same language, culture, and values. The purpose of this study is to expand our understanding of the linkages between women's culture and their information-seeking behaviour in the GCC region. The GCC includes conservative societies that impose strict restrictions on women. Female students, faculty members, and researchers have to comply with certain complex cultural rules while performing their professional activities. Although women in the GCC universities have witnessed quick technological advancements, their effort to seek information to develop their profession or career is undermined by gender segregation. Notably, it might seem that culture has a negative impact on women information-seeking behaviour in the region. Examining women's culture and their behaviour in seeking information is a challenging topic as it is very difficult to reach this sensitive group. A total of 2201 females in the GCC countries participated in the survey which included students of all levels, faculty member, researchers, and librarians. This self-response report has found significant cultural effects on the information-seeking behaviour of women in the GCC. Four objectives were laid down for the study to examine information needs, query formulation, task execution and women's interacting with systems. The survey was then conducted and found that culture significantly affects women information needs, query formulation, task execution and interacting with systems. Natural language terms are used to execute queries and tasks, while only popular databases used in the region or a particular university are used to interact with systems. Age, on the other hand, affects information-seeking behaviour in that at an early age, the person's information seeking behaviour is strongly affected by culture, but when the person gets older the effects decrease. The language also affects women query formulation and interacting with systems. The religious and cultural restrictions on Women preventing them from contacting foreign males (as Islamic culture insists) have been bypassed by the new electronic technology, and women directly feel free to contact any person of opposite gender through emails and social networks remaining physically segregated while electronically connected. Early exposure to the internet at the pre-university level is considered as an effect of this cultural shift in information-seeking behaviour.